Design of Temperature Control Coolant (International Journal of Engineering and Computer Science, 2017)
In this paper we will discuss about how we can create an artificial environment. In this Hi tech era Temperature plays an important part in our environment. Changes in temperature can affect the behaviour of human beings, plants and even materials such as semiconductors. This project is to control the temperature of a given environment such as baby incubator, industrial boiler, for automatic room temperature control, for creating artificial weather etc. A microcontroller is used to control the temperature in a circuit. Where the temperature had to be kept constant at particular value. The system will function as stated in the programming code of Atmega 8 in order to keep the temperature stable. A simple temperature controller which has least complex circuitry has to be designed so that it saves space and be more reliable for an incubator. Present design which uses microprocessor as main controller in digital signal processing combined with complex combinational logic circuit are redundant and needs to be improved in the sense of functionality. Hence, replacement of microprocessor with an microcontroller is prudent action due to its efficiency and reliability especially in an incubator and boiler.